Constructing a Narrative: The History of Science and Technology in Latin America - Portuondo, María M. (History compass, 2009)
This article provides a general introduction to the historiography of the history of science and technology in Latin America and presents an overview of the field's principal themes, with especial focus on how these have been addressed in English-language historical works. It engages the problems associated with constructing synthetic historical narratives and suggests ways of addressing these by using micro-histories to explain the relationship between the local, the national, and the transnational within the analytical framework afforded by intellectual history, history of science and of technology.